Research progress on protein tyrosine phosphatase A from Mycobacterium tuberculosis - Cai, Yifei; Zhang, Leiliang (Frontiers in Immunology, 2026)
Mycobacterium tuberculosis (Mtb) protein tyrosine phosphatase A (PtpA) is a crucial tyrosine phosphatase involved in the pathogenesis of tuberculosis. Structural analyses reveal that the W-loop and conserved cysteine residues are essential for the catalytic activity of PtpA, with modifications induced by reactive oxygen species playing a significant role in its function. PtpA suppresses key cellular processes, including phagosome-lysosome fusion and host cell apoptosis, while promoting ferroptosis and disrupting cytokine production to evade host immune responses. Its activity is enhanced by various post-translational modifications, including ubiquitination and phosphorylation, which facilitate its interactions with key cellular pathways. Recent research has identified several selective inhibitors that present promising therapeutic avenues against drug-resistant tuberculosis. This review synthesizes current knowledge on the characteristics, functions, and potential inhibitors of PtpA, underscoring its significance as a therapeutic target in the ongoing battle against tuberculosis and its associated challenges.